The impact of priming on dentally induced social judgements: An experimental study - Subramanian Sadhvi Shankar; Asimakopoulou Koula; Newton Tim; Chopra Anita; Luo Wen; Joiner Andrew (ELSEVIER SCI LTD, 2022)
Objective
To ascertain the effects of priming to consider tooth appearance (i.e. exposure to a ‘tooth whitening television advert’) versus control (a ‘non-dental’ television advert) on social judgements of tooth colour in a group of Caucasians.
Methods
Two groups of Caucasians randomly assigned to watch either a tooth-whitening advert (experimental, N = 67) or a bread advert (control, N = 62). All rated the measures of social perceptions: friendliness, popularity, social life, success, intelligence, graduation, introversion/extroversion, happiness, self-confidence, attractiveness, age-estimation and satisfaction, after watching either of the adverts and viewing three digitally modified photographs (Darkened, natural and whitened teeth) of different Caucasian adults (males and females) separately.
Results
There were no statistically significant differences for all the measures of social perception between the groups. Nevertheless, the questions that inquired about popularity, friendliness, success, intelligence, happiness, self-confidence, attractiveness and satisfaction were consistently rated higher for all three tooth shades in the experimental than the control groups. Further, within the experimental and control groups, higher ratings were given to the faces with whitened teeth than the natural and darkened teeth.
Conclusions
Priming has little impact on dentally induced social judgements as this study failed to demonstrate statistically significant differences. Nevertheless, both groups gave the highest subjective ratings for the faces with whitened teeth and the tooth-whitening advert group associated the faces in the photographs with higher subjective ratings than the non-dental advert group irrespective of the tooth shade. One reason for this could be the way media affects the psychological well-being.
Clinical significance statement
The almost universal exposure to idealised tooth appearance in the media may increase demand for aesthetic treatments. Standardising the colour of the tooth plays a huge impact and making individuals to view a tooth whitening advert just prior to a procedure might influence patient choices.